Experimental investigation of the check valve behaviour when the flow is reversing - Himr, Daniel; Habán, Vladimír; Hudec, Martin; Pavlík, Václav (EDP Sciences, 2017)
Check valve in a pipeline is supposed to prevent the reverse flow and to allow the flow in the positive direction. The construction of check valves follows these requirements, but the check valve must not cause pressure pulsations in transients. It means when the fluid is accelerating or decelerating. The article describes an experimental investigation of a swing check valve when the flow is changing its direction. The check valve was placed in an experimental circuit, where the pressure on the upstream and downstream side of the valve was measured and the current value of flow rate was determined. The goal was to simulate conditions in the real system, where the check valve slam had been observed.

Check valve in a pipeline is supposed to prevent the reverse flow and to allow the flow in the positive direction. The construction of check valves follows these requirements, but the check valve must not cause pressure pulsations in transients. It means when the fluid is accelerating or decelerating. The article describes an experimental investigation of a swing check valve when the flow is changing its direction. The check valve was placed in an experimental circuit, where the pressure on the upstream and downstream side of the valve was measured and the current value of flow rate was determined. The goal was to simulate conditions in the real system, where the check valve slam had been observed.
Experimental investigation of the check valve behaviour when the flow is reversing
Keywords: Check valves; Experimental investigations; Flow changes; Flow reversals; Pressure peaks; Pump trips; Check valves; Experimental investigations; Flow changes; Flow reversals; Pressure peaks; Pump trips